ANALISIS PELAKSANAAN PROGRAM BTQ (BACA TULIS AL-QUR’AN) TERHADAP PENINGKATAN NILAI KARAKTER RELIGIUS SISWA KELAS IV SDN TLOGOSARI WETAN 01 SEMARANG - Dewi Setiani; Arfilia Wijayanti; Sunan Baedowi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Qur’an Reading and Writing Program (BTQ) and its impact on improving the religious character values of fourth-grade students at SDN Tlogosari Wetan 01 Semarang. The research employed a descriptive qualitative approach, with data collected through observation, interviews, questionnaires, and documentation involving one BTQ teacher and 17 students as research subjects. The results show that the BTQ program is conducted regularly twice a week and has proven effective in enhancing students’ ability to read and write the Qur’an. The findings reveal an improvement in reading ability, with 65% of students reading fluently, 35% applying correct tajwid, and 29% articulating accurate makharijul huruf, while 71% of students are able to write hijaiyah letters properly. In addition, 78% of students demonstrated improvement in religious character, particularly in discipline, responsibility, and politeness, whereas 22% still require reinforcement in honesty and gratitude. Supporting factors include teacher commitment, adequate facilities, and student enthusiasm, while the inhibiting factors involve limited time, varied student abilities, and low parental support. The study concludes that the BTQ program plays a crucial role in shaping students’ religious character through consistent spiritual habituation and teacher modeling. It is recommended that schools enhance learning facilities, teachers adopt more innovative methods such as talaqqi and drill, and parents actively support their children’s Qur’anic practices at home.